Perforinopathy: A Spectrum of Human Immune Disease Caused by Defective Perforin Delivery or Function - Trapani, Joseph A.; Voskoboinik, Ilia (Frontiers in Immunology, 2013)
Congenital perforin deficiency is considered a rare cause of human immunopathology and immune dysregulation, and classically presents as a fatal illness early in infancy. However, we propose that a group of related disorders in which killer lymphocytes deliver only partially active perforin or a reduced quantum of wild-type perforin to the immune synapse should be considered part of an extended syndrome with overlapping but more variable clinical features. Apart from the many rare mutations scattered over the coding sequences, up to 10% of Caucasians carry the severely hypomorphic PRF1 allele C272 > T (leading to A91V mutation) and the overall prevalence of the homozygous state for A91V is around 1 in 600 individuals. We therefore postulate that the partial loss of perforin function and its clinical consequences may be more common then currently suspected. An acute clinical presentation is infrequent in A91V heterozygous individuals, but we postulate that the partial loss of perforin function may potentially be manifested in childhood or early adulthood as “idiopathic” inflammatory disease, or through increased cancer susceptibility – either hematological malignancy or multiple, independent primary cancers. We suggest the new term “perforinopathy” to signify the common functional endpoints of all the known consequences of perforin deficiency and failure to deliver fully functional perforin.